Navigating the Crisis of Transitional Justice in Post-Conflict Arab Regions: Challenges and Pathways to Reconciliation - Dashela, Adel (Biomed Journal of Scientific & Technical Research (BJSTR)., 2026)
This article discusses the transitional justice crisis in the Arab regions in the post-conflict phase and studies the implementation challenges and transitional justice mechanisms in areas suffering from conflict. It also explores the social and political factors that justice and reconciliation address and identifies the main difficulties determining transitional justice’s achievement. Focusing on case studies from Yemen, Morocco, and Mauritania, it attempts to provide a realistic view of the challenges to achieving transitional justice in post-conflict Arab regions.